Water management under extreme water scarcity: scenario analyses for the Jordan river basin, using WEAP21 [Water Evaluation and Planning] - Hoff H.; Swartz C.; Yates D.; Tielborger K. (Water saving in Mediterranean agriculture and future research needs [Vol. 2], 2007)
The WEAP (Water Evaluation and Planning) tool (see www.weap21.org) provides a consistent framework for integrating water availability, water demand, water quality and water use efficiency information from a range of sources from all riparian countries in the basin. With WEAP, we assess different climate, land use and population scenarios and adaptation options and combinations thereof, for their individual and overall effect on future water scarcity. By taking into account transboundary surface and ground water resources, we also assess the benefits from cooperative water management compared to separate national management. We find that climate change effects considerably constrain future water availability, while concomitant population growth, as derived from regional and global projections, greatly increases water demand. Several adaptation options are assessed and compared for their potential to close the widening gap. These include wastewater reuse, desalination, rainwater harvesting and artificial groundwater recharge, as well as demand management in different sectors. We are presently integrating green water and land management concepts into WEAP scenarios of sustainable development strategies, by including resulting changes in evapotranspiration and water productivity using external eco-hydrological models as well as internal simulation capabilities within WEAP.
Proceedings of the International Conference WASAMED Project (EU contract ICA3-CT-2002-10013), 2007/02/14-17, Valenzano (Italy)